Faktor Kualitas Pelayanan dalam Pengukuran Tingkat Kepuasan Masyarakat pada Bidang Pencegahan, Kesiapsiagaan, dan Pemadam Kebakaran Badan Penanggulangan Bencana Daerah Kabupaten Bogor : Studi Kasus di Kec. Cibinong Kab. Bogor - Maulita Lutfiani (Sanskara Manajemen Dan Bisnis, 2023)
This study aims to 1) find out how important the Field of Prevention, Preparedness and Fire Fighting at the Regional Disaster Management Agency of Bogor Regency is in the eyes of the public. 2) Analyze the level of community satisfaction with the Field of Prevention, Preparedness and Fire Fighting at the Regional Disaster Management Agency of Bogor Regency. 3) Analyzing the community's response to the Prevention, Preparedness and Fire Fighting Division of the Bogor Regency Disaster Management Agency. The scope of this research is the factors related to the level of community satisfaction in the field of Prevention, Preparedness and Fire Fighting at the Regional Disaster Management Agency of Bogor Regency (a case study in Cibinong District, Bogor Regency). This research This research is descriptive in nature, while the method for obtaining data is done by survey method. The techniques used in data collection are library research and field research. The results of the study show that 1) the Prevention, Preparedness and Fire Fighting Division of the Bogor Regency Regional Disaster Management Agency plays an important role in people's lives, this can be seen (100%) the people say it is important. 2) The services provided by the Prevention, Preparedness and Fire Fighting Division of the Bogor Regency Regional Disaster Management Agency can be carried out well because there are supporting aspects such as smooth contact with the fire department, facilities owned by the fire department and personnel who are ready standby on duty. 3) The community's response to the services provided by the Prevention, Preparedness and Fire Fighting Division of the Bogor Regency Regional Disaster Management Agency was very good, namely (100%) the people who had been handled by the Prevention, Preparedness and Fire Fighting Division of the Bogor Regency Regional Disaster Management Agency expressed satisfaction with services that have been provided.